Global Experiences of Spirituality, Religion and Secular Enthusiasm in our Organizational Practice: A Discovery - Saman, Osama El (Journal for the Study of Spirituality, 2014)
We are a group of doctoral students studying organizational change. We were surprised that discussions about spirituality arose early in our group discussions. In our session at the Third International BASS Conference on Spirituality in a Challenging World, we told the story of our engagement with spirituality, as a group and as individuals. We invited participants to join our conversation and to reflect with us on the ways in which spirituality emerges in work settings and conversations. This paper describes the session and points to some of its implications. We suggest that the session itself demonstrated how discussion of spirituality in a safe, compassionate environment expands the quality of conversation, and creates deeper levels of connection and trust among those involved.